Tooth agenesis patterns and variants in PAX9: A systematic review - Narin Intarak; Karn Tongchairati; Kittipat Termteerapornpimol; Soranun Chantarangsu; Thantrira Porntaveetus (Elsevier, 2023)
Mutations in PAX9 are the most common genetic cause of tooth agenesis (TA). The aim of this study was to systematically review the profiles of the TA and PAX9 variants and establish their genotype-phenotype correlation. Forty articles were eligible for 178 patients and 61 mutations (26 in frame and 32 null mutations). PAX9 mutations predominantly affected molars, mostly the second molar, and the mandibular first premolar was the least affected. More missing teeth were found in the maxilla than the mandible, and with null mutations than in-frame mutations. The number of missing teeth was correlated with the locations of the in-frame mutations with the C-terminus mutations demonstrating the fewest missing teeth. The null mutation location did not influence the number of missing teeth. Null mutations in all locations predominantly affected molars. For the in-frame mutations, a missing second molar was commonly associated with mutations in the highly conserved paired DNA-binding domain, particularly the linking peptide (100% prevalence). In contrast, C-terminus mutations were rarely associated with missing second molars and anterior teeth, but were commonly related to an absent second premolar. These finding indicate that the mutation type and position contribute to different degrees of loss of PAX9 function that further differentially influences the manifestations of TA. This study provides novel information on the correlation of the PAX9 genotype-phenotype, aiding in the genetic counseling for TA.